GANGGUAN FUNGSIONAL MENETAP BERPENGARUH PADA RISIKO DEPRESI LANSIA DM DI WILAYAH KERJA PUSKESMAS JEKAN RAYA KOTA PALANGKA RAYA - Agnes Dewi Astuti; Reny Sulistyowati; Natalansyah Natalansyah (Jurnal Kesehatan Manarang, 2017)
Aging is a a natural process in life. Aging is characterized by loss of slowly ability organ tissue repair itself and is irreversible. The elderly are the final statge of a person’s life cycle and experience the aging process with change in various physical or physiological, psychological and social aspects (Miller, 2012). Hanges dues to aging eldely comple raises enormous opportunity for the elderly are at risk of depression. The objective of this study was to determine the factors that influence the risk of depression in elderly at Puskesmas Jekan Raya of Palangka Raya City with descriptive correlational research design using cross sectional approach. The sampling technique in this research is by using probability sampling technique that sampling technique giving equal oppurtinity to every individual in the population to be the research sample.The statistical test used was descriptive test and Chi Square test. The result indicate that factors influencing the risk of depression in the elderly is functional impairment were settled with p value= 0,000. Conclusion of the elderly who have other diseases besides DM settle a vulnerable population at risk of depression. The most dominant factor is the functional disturbances persist after controlling the variable of age, live event s and other diseases (other than DM) with OR=39. Recommended in elderly nursing decision making in order to improve the health of elderly family based programs to prevent depression in the elderly and especially carring by elderly family members.